Interspecies Competitive Interactions of Clinical Isolates of Acinetobacter baumannii With Klebsiella pneumoniae, Staphylococcus aureus, and Pseudomonas aeruginosa - Qutaiba Ababneh; Rahaf Alqazaq; Ziad Jaradat; Hala Khanjar (International Journal of Clinical Practice)
Many microbial infections are caused by multiple species. However, little is known about the detailed interactions and mechanisms underlying competition between coexisting pathogens. Acinetobacter baumannii is a major nosocomial pathogen that is often involved in mixed infections. To date, few studies have focused on the interactions between A. baumannii and other common coinfectious microbes. In this study, we aimed to investigate the interspecies competition among clinical A. baumannii isolates with Klebsiella pneumoniae, Staphylococcus aureus, and Pseudomonas aeruginosa. A. baumannii isolates were recovered from 56 patients in three major hospitals in Jordan between 2018 and 2019. The isolates were obtained from various clinical specimens, including sputum, wound, blood, and urine. Clinical isolates of methicillin-resistant S. aureus, P. aeruginosa, and K. pneumoniae were also used. Interactions between A. baumannii isolates and each of the other species were investigated through 168 interspecies competition assays, and each experiment was done in duplicate. The results revealed that A. baumannii outcompeted K. pneumoniae, significantly reducing its growth, with the degree of reduction varying depending on the clinical origin of the A. baumannii isolates. Moreover, the growth of S. aureus was decreased regardless of the A. baumannii clinical origin, with a higher reduction compared to K. pneumoniae. On the other hand, the presence of P. aeruginosa led to a significant decrease in the A. baumannii growth, while the growth of P. aeruginosa was significantly increased after coculture with A. baumannii. The present study provides evidence that the A. baumannii isolates have competitive advantages over both S. aureus and K. pneumoniae. In contrast, P. aeruginosa outcompetes A. baumannii isolates. Our findings provide new insights to identify potential therapeutics to control coinfections.